2015
DOI: 10.1016/j.molonc.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeted capture massively parallel sequencing analysis of LCIS and invasive lobular cancer: Repertoire of somatic genetic alterations and clonal relationships

Abstract: Purpose Lobular carcinoma in situ (LCIS) has been proposed as a non-obligate precursor of invasive lobular carcinoma (ILC). Here we sought to define the repertoire of somatic genetic alterations in pure LCIS and in synchronous LCIS and ILC using targeted massively parallel sequencing. Methods DNA samples extracted from microdissected LCIS, ILC and matched normal breast tissue or peripheral blood from 30 patients were subjected to massively parallel sequencing targeting all exons of 273 genes, including the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 50 publications
(68 reference statements)
1
32
0
Order By: Relevance
“…It did, however, show that activating PIK3CA mutations are as common in LCIS as CDH1 mutations. Activating PIK3CA mutations are well-described in both ILC and IDC, occurring in 48% of ILC (as the second most common mutations after CDH1 ) and 33% of IDC [47, 48]. PIK3CA mutations have previously been reported by Christgen et al [49] in 1/3 patients with LCIS associated with ILC and by Sakr et al [48] in 7/19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It did, however, show that activating PIK3CA mutations are as common in LCIS as CDH1 mutations. Activating PIK3CA mutations are well-described in both ILC and IDC, occurring in 48% of ILC (as the second most common mutations after CDH1 ) and 33% of IDC [47, 48]. PIK3CA mutations have previously been reported by Christgen et al [49] in 1/3 patients with LCIS associated with ILC and by Sakr et al [48] in 7/19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Activating PIK3CA mutations are well-described in both ILC and IDC, occurring in 48% of ILC (as the second most common mutations after CDH1 ) and 33% of IDC [47, 48]. PIK3CA mutations have previously been reported by Christgen et al [49] in 1/3 patients with LCIS associated with ILC and by Sakr et al [48] in 7/19 patients. We confirmed the frequency of PIK3CA mutations in a larger set of LCIS by Sanger sequencing, which revealed no difference in the frequency of PIK3CA mutations in inv-cLCIS compared to pure-cLCIS.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, targeted capture and MPS technologies have been widely used in clinical practice and have got satisfactory results15232425262728. To this end, we designed the gene panel contains 118 genes which are reported to be associated with leukoencephalopathies, not only contains genes associated with genetic leukoencephalopathy, but also mitochondrial disease, cerebral cortical degenerative disorders, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in CDH1 have been identified in up to 56% of cases of LCIS, with matching CDH1 mutations in adjacent ILBC 52 55. Frequent mutations are also found in PIK3CA and CBFB in LCIS with shared mutations in 71% of coexistent ILBC indicating that the lesions are clonally related 52. Another study by the same group identified 169 genes that were differentially expressed in the progression pathway from normal epithelium to LCIS to ILBC; interestingly there was enrichment for genes located on 16q and 1q, sites of common copy number changes in lobular carcinoma 56.…”
Section: Lobular Breast Tumorigenesis With Cdh1 Defectmentioning
confidence: 97%